2013
DOI: 10.1002/cctc.201200582
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Phenol and Derivatives over an Ionic Liquid‐Like Copolymer Stabilized Nanocatalyst in Aqueous Media

Abstract: Using phenolic bio‐oil as feedstock for sustainable production of alkane fuels is of great significance. Here, the hydrodeoxygenation of phenol and its derivatives has been systematically investigated in aqueous media with a dual‐functional catalyst system consisting of water‐soluble, ionic liquid‐like copolymer A‐stabilized nanocatalysts and the mineral acid H3PO4. The developed Ru/A‐H3PO4 catalyst system achieved a complete phenol conversion with cyclohexane selectivity higher than 99 %, making it by far one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…For the 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 catalysts, the conversion of phenol was 97.3 % and the selectivity of cyclohexane was 73.7 %. The yield of cyclohexane (71.7 %) over 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 was much higher than that of the other three catalysts and those reported previously, which confirmed that there are distinct synergistic effects of oxygen vacancies in NiO x for hydrogenation and Lewis acid sites in Ni 2 P for deoxygenation (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…For the 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 catalysts, the conversion of phenol was 97.3 % and the selectivity of cyclohexane was 73.7 %. The yield of cyclohexane (71.7 %) over 3.1 % NiO x ‐6.9 % Ni 2 P/SiO 2 was much higher than that of the other three catalysts and those reported previously, which confirmed that there are distinct synergistic effects of oxygen vacancies in NiO x for hydrogenation and Lewis acid sites in Ni 2 P for deoxygenation (Figure ).…”
Section: Resultssupporting
confidence: 78%
“…593 It has been demonstrated numerous times that cyclohexanes can be acquired in high yields from methoxylated phenols through the combined action of both metal catalysis (hydrogenation) and Brønsted acidity (dehydration and/or demethoxylation). 244,[594][595][596][597][598][599][600][601][602][603][604] Noble metals (Ru, Rh, Pd, Pt) have been shown to provide excellent hydrogenation activity in these transformations, but also cheaper Ni-based catalyst have been applied successfully. The acidic counterpart of the bifunctional system can be provided by homogeneous acids (e.g.…”
Section: Chemocatalytic Upgrading Of Phenolic Compoundsmentioning
confidence: 99%
“…[28][29][30] Dyson and coworkers, and others, have applied these systems as catalysts in reactions such as hydrodeoxygenation (HDO) of phenol to cyclohexane, and regioselective hydrogenation of toluene to methyl cyclohexene in imidazolium ILs. [31][32][33] Other protocols also exist for similar conversions, using metal or metal oxide catalysts in different IL media, but to the best of our knowledge, tetraalkylphosphonium ILs have not been used for metal NP-catalysed aromatic hydrogenations, despite their NP-stabilizing abilities and chemical inertness to a variety of reagents. 34,35 In this work, we show the synthesis and stabilization of catalytically active precious metal NPs in a variety of tetraalkylphosphonium ILs.…”
Section: Introductionmentioning
confidence: 99%